2003
DOI: 10.1038/sj.cdd.4401173
|View full text |Cite
|
Sign up to set email alerts
|

ΔFosB, but not FosB, induces delayed apoptosis independent of cell proliferation in the Rat1a embryo cell line

Abstract: The fates of Rat1a cells expressing FosB and DFosB as fusion proteins (ER-FosB, ER-DFosB) with the ligand binding domain of human estrogen receptor were examined. The binding of estrogen to the fusion proteins resulted in their nuclear translocation and triggered cell proliferation, and thereafter delayed cell death was observed only in cells expressing ER-DFosB. The proliferation of Rat1a cells, but not cell death triggered by ER-DFosB, was completely abolished by butyrolactone I, an inhibitor of cyclinedepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 49 publications
1
26
0
2
Order By: Relevance
“…We recently identified galectin-1 to be a secretory factor whose expression is induced by DFosB in embryonic cell lines, [20][21][22] and we herein showed the expression of galectin-1 to be significantly upregulated in the embryonic cortical cells by either FosB or DFosB, as well as in the hippocampus after ischemia. Furthermore, our data also indicate that galectin-1, as a secretory factor from FosB-or DFosB-expressing cells, appears to promote the proliferation of embryonic cortical cells.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…We recently identified galectin-1 to be a secretory factor whose expression is induced by DFosB in embryonic cell lines, [20][21][22] and we herein showed the expression of galectin-1 to be significantly upregulated in the embryonic cortical cells by either FosB or DFosB, as well as in the hippocampus after ischemia. Furthermore, our data also indicate that galectin-1, as a secretory factor from FosB-or DFosB-expressing cells, appears to promote the proliferation of embryonic cortical cells.…”
Section: Discussionsupporting
confidence: 50%
“…We previously demonstrated that an artificial expression of DFosB, and to a lesser extent FosB, triggers DNA replication and cell division in quiescent fibroblast cells in the absence of serum. [18][19][20][21] Furthermore, neurogenesis in the adult mammalian brain has been proven to occur in the SVZ and DG of the hippocampus, and it is likely to be promoted by stress such as ischemic insult.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations